A Survey on Operating System Support for Embedded Systems Properties - Friedrich, Luís Fernando (Anais do Workshop de Sistemas Operacionais (WSO); 2009: Anais do VI Workshop de Sistemas Operacionais, 2009)
We can find a large variety of applications where embedded systems play an important role, from small standalone systems, like a network router, to complex distributed realtime embedded systems (DRE) supporting several large scale missioncritical domains as avionic applications. The rapid progress in processor and sensor technology combined with the expanding diversity of application fields is placing enormous demands on the facilities that software infrastructure like operating systems must provide. The paper presents an examination of how some of the important properties of embedded systems has being supported by operating system infrastructure.